Teresa Bürge and Peter M. Fischer (eds),The Decline of Bronze Age Civilisations in the Mediterranean: Cyprus and Beyond. Studies in Mediterranean Archaeology 154. - Alvarez, Laura E. (Journal of Greek Archaeology, 2025)
The rise-and-fall of civilisations paradigm is intellectually sexy, as it makes that provocative and emotional claim that flourishing societies can, or appear to, ‘abruptly’ take new directions, and it is without any doubt that a volume titled The Decline of Bronze Age Civilisations in the Mediterranean: Cyprus and Beyond would be approached with excitement by anyone interested in the historical change of human conditions, although especially within academic circles. Product of a 2020 meeting held in Gothenburg, Sweden, organised within the framework of a larger research project (2016–2021) led by Peter M. Fischer on The Collapse of Bronze Age Societies in the Eastern Mediterranean, this imposing and beautifully edited volume of nineteen chapters, edited by Peter M. Fischer and Teresa Bürge, brings together fifteen papers delivered at this workshop, alongside three additional contributions from external scholars. Collectively, nineteen chapters invite a broad reconsideration of the transformation, weakening or utter collapse and its aftermath of Bronze Age cultures throughout the Aegean, Anatolia, Syria-Palestine, and Egypt, around the twelfth century BCE. Each chapter is consistently and generously illustrated, with a well-curated selection of colour maps, photographs and line drawings enhancing the visual and scholarly appeal.